2014
DOI: 10.1186/1866-1955-6-14
|View full text |Cite
|
Sign up to set email alerts
|

Reactivity to fearful expressions of familiar and unfamiliar people in children with autism: an eye-tracking pupillometry study

Abstract: BackgroundIndividuals with autism are often reported to have difficulty with emotion processing. However, clinical and experimental data show that they are sensitive to familiarity; for example, they show normative attachment to familiar people, and have normative brain activity in response to familiar faces. To date, no study has measured their reactivity to the emotions of familiar vs. unfamiliar people. Thus, our aim was to determine whether individuals with autism would show normative reactivity to emotion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
48
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 62 publications
(59 citation statements)
references
References 109 publications
(106 reference statements)
7
48
3
Order By: Relevance
“…Although the TD children were expected to have greater pupil dilation to unfamiliar compared to familiar people based on previous findings (Nuske et al 2014a;Stephan and Stephan 1985), we did not confirm this hypothesis. The children with ASD, however, did show greater pupil dilation to unfamiliar people than familiar people, across gaze conditions, which is consistent with the idea that unfamiliar people create more anxiety than familiar people in some groups of people (Stephan and Stephan 1985).…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…Although the TD children were expected to have greater pupil dilation to unfamiliar compared to familiar people based on previous findings (Nuske et al 2014a;Stephan and Stephan 1985), we did not confirm this hypothesis. The children with ASD, however, did show greater pupil dilation to unfamiliar people than familiar people, across gaze conditions, which is consistent with the idea that unfamiliar people create more anxiety than familiar people in some groups of people (Stephan and Stephan 1985).…”
Section: Discussioncontrasting
confidence: 55%
“…Nuske et al (2014a) found that typically-developing (TD) children have greater pupil dilation (increased emotional arousal) to emotional facial expressions in unfamiliar people compared to familiar people, but this was not the case for children with ASD. Conversely, in the only published study that has measured emotional arousal to mutual versus averted gaze in familiar and unfamiliar people, KylliĂ€inen et al (2012) found that both children with ASD and TD children had greater SCRs to familiar compared to unfamiliar people.…”
Section: Emotional Arousal To Mutual Gaze In Familiar Peoplementioning
confidence: 93%
“…Since then, pupillometry has been used to examine a number of questions in ASD (and children at risk for ASD) including those related to resting-state physiology [46–48], sensory-processing [49, 50], eye-gaze processing [51] and general face processing [52]. Pupillometry findings on emotion processing in ASD are consistent with findings from on older, more-able children and adults, including finding reduced and delayed emotional responses in the population [24, 30, 53–55]. …”
Section: Introductionmentioning
confidence: 79%
“…However, there was a clear gaze preference for angry over neutral faces at the 500 ms point in both groups of participants, suggesting that a dot-probe version of this task would also have indicated a significant attentional preference towards angry faces for both groups. Finally, we removed fixations with a duration shorter than 100 ms to be consistent with previous eyetracking research in clinical psychology (e.g., Gamble and Rapee 2009) and eyetracking research with preschool aged children (Nuske, Vivanti, and Dissanayake 2014). However, it is not clear how much information children of this age can extract in 100 ms; a shorter or longer fixation duration cut-off may be more appropriate for this age-group.…”
Section: Strengths and Limitationsmentioning
confidence: 85%